Evaluating the impact of ‘rehabilitative adjudications’ in four English prisons - Fitzalan Howard, Flora (Psychology, crime & law, 2021)
Effective responses to rule-breaking in prison are critical for maintaining safety, stability and order. This study explored the impact of rehabilitative adjudications, in which rehabilitative skills and procedural justice (PJ) principles are used explicitly within a traditional disciplinary process for responding to rule-breaking. A trial in four prisons brought evidence of improved prisoner perceptions of PJ and stronger intentions to comply with rules and regulations. While no significant improvements in more serious custodial conduct were identified, the findings support the use of this concept within a wider prison approach to underpin a culture characterised by fairness and hope – both well-evidenced features of prisons that enable rehabilitation and desistance.